How and when workplace ostracism influences task performance: Through the lens of conservation of resource theory. (18th February 2019) - Xia, Aijing; Wang, Bin; Song, Baihe; Zhang, Wei; Qian, Jing
Abstract: Drawing upon the conservation of resource (COR) theory, this study examines how workplace ostracism negatively affects task performance by reducing workers' physical strength and emotional energy; it also captures the moderating role of spousal support in the relationship between ostracism, physical strength, and emotional energy. Using matched data from 117 supervisors and 523 of their immediate employees, results indicated that workplace ostracism negatively related to physical strength and emotional energy, which, in turn, decreased task performance. Additionally, spousal support mitigated the harmful impact of workplace ostracism on individual emotional energy, whereas its buffering effect on physical strength was not significant. Theoretical and practical implications are discussed.